2015
DOI: 10.1002/chem.201500281
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Spectroscopic and Computational Examination of the Dative Interaction in Constrained Phosphine–Stibines and Phosphine–Stiboranes

Abstract: A series of phosphine-stibine and phosphine-stiborane peri-substituted acenaphthenes containing all permutations of pentavalent groups -SbCln Ph4-n (5-9), as well as trivalent groups -SbCl2 , -Sb(R)Cl, and -SbPh2 (2-4, R=Ph, Mes), were synthesised and fully characterised by single crystal diffraction and multinuclear NMR spectroscopy. In addition, the bonding in these species was studied by DFT computational methods. The P-Sb dative interactions in both series range from strongly bonding to non-bonding as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 62 publications
10
54
0
1
Order By: Relevance
“…His analysis shed light in to the existence of weak boron‐bonds, though the continuum nature of 2‐centre 2‐electron and Z‐bond was not obvious. Very recently Chalmers et al, observed the strong‐bond to dative‐bond and further to no‐bond interactions in constrained P‐‐‐Sb systems as the Lewis acidity of the acceptor decreases . Similar observations can be made about the course of atom abstraction reactions, chemical reaction mechanisms or nucleophilic substitution reactions published in recent times.…”
Section: Continuum Nature Of Bondingsupporting
confidence: 60%
“…His analysis shed light in to the existence of weak boron‐bonds, though the continuum nature of 2‐centre 2‐electron and Z‐bond was not obvious. Very recently Chalmers et al, observed the strong‐bond to dative‐bond and further to no‐bond interactions in constrained P‐‐‐Sb systems as the Lewis acidity of the acceptor decreases . Similar observations can be made about the course of atom abstraction reactions, chemical reaction mechanisms or nucleophilic substitution reactions published in recent times.…”
Section: Continuum Nature Of Bondingsupporting
confidence: 60%
“…Short P–Sb separations have also been observed in derivatives in which the two moieties are linked by a peri -naphthalene linker such as 5-(Ph 2 P)–6-(Cl 2 Sb)–Ace (2.808(1) Å) or 5-( i Pr 2 P)–6-(Cl 2 Ph 2 Sb)–Ace (2.9925(8) Å, Ace = acenaphthylene). 60 Although these P–Sb distances are comparable to those measured in 5 and 7 , it can be expected that the strain imposed by the use of the ortho -phenylene backbone will fragilize this linkage, opening the door for reactivity in the P/Sb pocket.…”
Section: Resultsmentioning
confidence: 70%
“…Deuterated benzene was dried with activated molecular sieves (4 Å) and degassed prior to use. Starting materials LAl, [ 13 ] LGa, [ 14 ] LIn, [ 15 ] PhAsCl 2 , [ 41 ] PhSbCl 2 , [ 42 ] and KCp* [ 43 ] were prepared according to literature procedures. NMR spectra ( δ in ppm) were recorded using a Bruker Avance DPX 300 ( 1 H 300.1 MHz, 13 C{ 1 H} 75.5 MHz) or a Bruker Avance Neo 400 ( 1 H 400.1 MHz, 13 C{ 1 H} 100.6 MHz) spectrometer and were referenced to internal C 6 D 5 H ( 1 H δ = 7.16, 13 C δ = 128.06) or C 6 D 5 CD 2 H ( 1 H δ = 2.08, 13 C δ = 20.43).…”
Section: Methodsmentioning
confidence: 99%